Analysing the Design Criteria of Public Open Spaces for the Disabled Persons: An Evaluation of Kumsal Park in Northern Cyprus - Erçin, Çilen; Al Hindwan, Ibtihal (European Journal of Sustainable Development, 2023)
Every person, regardless of their race, culture, origin, or religion, has an inherent right to move and live comfortably in various environments. This principle extends universally to include individuals with disabilities. It is crucial to recognize and uphold the rights of disabled individuals to equal access, participation, and inclusion in all aspects of life, including physical environments, public spaces, transportation, communication, and social interactions. By promoting inclusivity and eliminating barriers, society can create a fairer and more accessible world that allows people with disabilities to fully engage in their rights as valued members of the community. Hence, it is crucial to guarantee the convenient accessibility of all public areas since they play a substantial part in our everyday experiences. The objective of the research paper is to examine the standards for designing POS, particularly emphasizing their appropriateness for people with disabilities. The study conducts a comprehensive evaluation of Kumsal Park's design elements, assessing whether they adequately consider the needs of disabled individuals. The data collection involves a structured questionnaire that covers demographics, general information about Kumsal Park, park design features, and design criteria for individuals with disabilities. Additionally, data is collected through observations using a checklist created based on the study's observations. While Kumsal Park in Nicosia, Northern Cyprus, demonstrates satisfactory design criteria in certain areas, improvements are required to cater to disabled individuals and enhance the overall park experience. Addressing the identified issues, such as lighting, parking, security, activities, and signage, and improving accessibility features will contribute to creating a more inclusive and satisfying environment for all visitors. Keywords: design criteria, public open spaces, parks, disabled persons, universal design, Kumsal Park, Northern Cyprus.